‘YorMeme’ for the girl, boy, bakla, tomboy plus a discourse analysis of Vice Ganda’s commentaries during the 2020–2024 Duterte-Marcos era - Pacinos, Matthew Aaron N.
As the present media landscape navigates various socio-political issues, the representation of the Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual (LGBTQIA+) community remains to be challenged both by the current political climate and the Philippines’ religious-cultural setting. Conveniently, such a representation finds strength through the persona of the openly gay and unkabogable Vice Ganda who is at the forefront of the LGBTQIA+ discourse as one of the country’s contemporary celebrity superstars. However, existing studies limit Vice Ganda’s influence on issues related to gender, queer visibility, and comedy, thereby failing to establish the symbolic power of Vice Ganda and its potential to transcend to the political realm.